2012
DOI: 10.2975/35.4.2012.337.340
|View full text |Cite
|
Sign up to set email alerts
|

Challenges faced by mental health peer support workers: Peer support from the peer supporter's point of view.

Abstract: Managers have a responsibility to be informed about the peer support worker role and communicate role related information to other team members to ensure that peer support workers are included as part of the health team. Implications for practice therefore center on training for managers and inclusion of the peer support worker role in orientation programs. Further, if these steps are not undertaken, a valuable resource could be lost to a health service to the detriment of persons with a mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
126
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 10 publications
8
126
0
3
Order By: Relevance
“…In one study, participants found it a challenge to know how to disclose, how much to disclose and when it was appropriate to disclose personal information to clients (Kemp and Henderson 2012). Issues have also been raised about how close peer workers should get with other peer workers that they work with and how this could present difficulties when resuming to a more therapeutic relationship within a work context (Coleman and Campbell 2009).…”
Section: Introductionmentioning
confidence: 94%
“…In one study, participants found it a challenge to know how to disclose, how much to disclose and when it was appropriate to disclose personal information to clients (Kemp and Henderson 2012). Issues have also been raised about how close peer workers should get with other peer workers that they work with and how this could present difficulties when resuming to a more therapeutic relationship within a work context (Coleman and Campbell 2009).…”
Section: Introductionmentioning
confidence: 94%
“…More specifically, managers can support peer workers in team meetings, provide peer workers with access to other organisational support and increase opportunities for peer workers to support one another. 44 Repper and Carter 17 conclude their review by highlighting the importance of dedicated training and support for the peer worker role. v. Valuing the peer worker role Mowbray and colleagues 49 note that peer workers may experience feelings of being part of the team, but also of lower status in comparison with other members of the team.…”
Section: The Existing Evidence On Peer Worker Roles In Mental Health mentioning
confidence: 99%
“…As such, it is also seen as important for both managers and team members to receive information about the role of a peer worker through the creation of a peer support manual or handbook. 44 vi. Relationships with service users A number of studies demonstrate how peer workers offer a unique relationship to service users in comparison with other mental health professionals.…”
Section: The Existing Evidence On Peer Worker Roles In Mental Health mentioning
confidence: 99%
See 1 more Smart Citation
“…There is qualitative evidence that suggests that the absence of a clear job description for peer workers creates challenges for team working (Kemp 2012). In a survey of managerial and human resources staff in agencies employing peer workers in the USA, role conflict and confusion, allied to poorly defined job structure, were identified as undermining role integration (Gates 2007).…”
Section: Distinctiveness Of the Peer Worker Rolementioning
confidence: 99%